2018
DOI: 10.1111/cdep.12292
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and Learning Spelling

Abstract: Learning to spell is important for writing and reading, but how spelling should be taught is a controversial topic. Although children learn about spelling to some extent as they encounter words while reading, this is not usually enough to make them good spellers. Children need systematic spelling instruction to learn how the writing system works and not just memorize how words are spelled. Phonics instruction is more effective than some other instructional approaches, but teaching phonics presents a simplified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 25 publications
2
32
0
5
Order By: Relevance
“…Correlation and regression analyses further indicated that the impact of morphological awareness on spelling increased from third to fourth grade. This supports the idea that morphological awareness gets more important with literacy experience and increases once phoneme-grapheme correspondences are mastered and the correct spelling of a word relies on the use of larger written language units (Kirby et al 2012;Treiman 2018).…”
Section: Discussionsupporting
confidence: 73%
“…Correlation and regression analyses further indicated that the impact of morphological awareness on spelling increased from third to fourth grade. This supports the idea that morphological awareness gets more important with literacy experience and increases once phoneme-grapheme correspondences are mastered and the correct spelling of a word relies on the use of larger written language units (Kirby et al 2012;Treiman 2018).…”
Section: Discussionsupporting
confidence: 73%
“…And yet again, the design of the meta-analysis did not assess whether systematic phonics was more effective than unsystematic phonics (let alone show that systematic phonics is more effective than the alternative methods they did investigate). Nevertheless, the metaanalysis is frequently cited as evidence in support of systematic phonics over whole language (e.g., Lim and Oei 2015;Treiman 2018;Van der Kleij et al 2017).…”
Section: Galuschka Et Al (2014)mentioning
confidence: 99%
“…There is experimental evidence that skilled and developing spellers show sensitivity to all of these patterns (Treiman, 2018) and artificial lexicon studies have begun to explore whether this is underpinned by statistical learning processes akin to those thought to play a role in spoken language acquisition. However, a limitation is that no study has conclusively demonstrated the learning of purely visual graphotactic spelling patterns in children controlling for the possibility that learning could be underpinned by processes operating over spoken language.…”
Section: Statistical and Explicit Learning Of Graphotactic Patterns Wmentioning
confidence: 99%